Efektivitas Konseling Kelompok Tekhnik Cognitive Restructuring Untuk Meningkatkan Konsep Diri Siswa di SMK Negeri Singaraja - Megawati Ricky; I Ketut Gading; Putu Ari Dharmayanti (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This study expects to decide the viability of the Mental Rebuilding Gathering Directing strategies to further develop understudies' reasoning power. The study's design included a brief assessment and a group-control plan for the pre-test. The number of inhabitants in this review were understudies of class XI Friendliness SMK N 1 Singaraja what's more, a sum of 3 classes. Examining was finished through purposive testing. The students in class XI-PH 7, which served as the experimental class and the control class, were the members of the sample. The SPSS 25.0 Windows program was utilized for the t test and Effect Size data analysis techniques. Data The questionnaire is a self-concept questionnaire, so this study uses one of them to improve students' self-esteem through cognitive rehabilitation.concept in Singaraja at SMK N 1. In view of the finishes of this study one might say furthermore, this sort of counsel is powerful. The aftereffects of this study got t = 19.53 Responsiveness = 10.15 p > 0.05, one might say that Ha and Ho are dismissed.